Secured Data Transmissions In Manet Using Neighbor Position Verfication Protocol (International Journal of Engineering and Computer Science, 2014)
In mobile ad hoc network, Position aided routing protocols can offer a significant performance increase over traditional ad hoc routing protocols. As position information is broadcasted including the enemy to receive. Routes may be disconnected due to dynamic movement of nodes. Such networks are more vulnerable to both internal and external attacks due to presence of adversarial nodes. These nodes affect the performance of routing protocol in ad hoc networks. So it is essential to identify the neighbours in MANET. The “Neighbor Position Verification” (NPV), is a routing protocol designed to protect the network from adversary nodes by verifying the position of neighbor nodes to improve security, efficiency and performance in MANET routing